Evaluasi Kualitas Tanah di Kabupaten Cianjur, Jawa Barat - Eka Wardhani; Shafira Rizki Safwani (Fakultas Teknik, 2023)
Soil components consisting of solids, water and air are the main natural resources that greatly affect life. The ability of soil as a growing medium will be optimal if it is supported by physical, chemical and biological properties as an indicator that shows the level of soil fertility. Soil quality is the capacity of a soil in a field to provide the functions needed by humans or natural ecosystems for a long time. Soil quality can be measured based on soil quality indicators. The decrease in the ability of the soil to carry out its various functions indicates that the quality of the soil has been disturbed which has resulted in an increase in critical land, a decrease in soil productivity and environmental pollution. This study aims to analyze the soil quality in the Cianjur Regency. The data used in this study is secondary data from the Environmental Service of Cianjur Regency in 2019. Sampling was carried out in 6 sub-districts, namely Pacet, Sukaresmi, Cipanas, Cianjur, Cugenang and Karangtengah. Based on the results of field data analysis that has been obtained, there are several indicators that are assessed as critical thresholds that have been determined, namely, Fraction Composition, Porosity, Permeability and Redox Value. All sample locations were categorized as Slightly Damaged and there were various scoring scores ranging from 10 (highest score) and 4 (lowest score). Management can be done using several methods, namely mechanical, vegetative and chemical.